Exploring the Prevalence of Dry Eye Disease and Its Impact on Quality of Life in Saudi Adults: A Cross-Sectional Investigation - Mohammad A. Jareebi; Ayman A. Akkur; Dhiyaa A. H. Otayf; Ahmed Y. Najmi; Osama A. Mobarki; Eyad Z. Omar; Mohammed A. Najmi; Ali Y. Madkhali; Nasser A. N. Abu Alzawayid; Yasir M. Darbeshi; Abdulaziz Ali Alagsam; Ali Alabbas Ahmad Alhazmi; et al. (Medicina, 2025)
Background and Objectives: Dry eye disease (DED) is a multifactorial condition that affects quality of life (QoL). Symptoms like discomfort, blurred vision, and light sensitivity can negatively impact work efficiency, productivity, and psychological well-being. This study aimed to examine the relationship between DED and QoL, identify risk factors, and estimate DED prevalence in Saudi Arabia. Materials and Methods: This cross-sectional study included 1062 participants from Saudi Arabia, recruited via convenience sampling. Data were collected using an online questionnaire with three sections: sociodemographic information, the ocular surface disease index (OSDI) to assess DED severity, and the Arabic WHOQOL-BREF questionnaire to evaluate QoL. Results: Among participants, 77% suffered from DED. Males (β = −9.18, p < 0.001), postgraduate degree holders (β = −13.86, p = 0.001), and individuals with income >15,000 SR (β = −5.10, p = 0.023) had lower OSDI scores compared to reference groups (females, those with high school education or lower, and those with income <5000 SR, respectively), indicating a lower DED risk. Employed individuals, students (employed: β = 10.78, p < 0.020; students: β = 10.60, p < 0.016), divorced/widowed individuals (β = 18.70, p < 0.003), and those with diabetes, hypertension, and thyroid disorders showed higher OSDI scores. Higher OSDI scores correlated with lower QoL scores across all domains (physical: β = −0.26, p < 0.001; psychological: β = −0.22, p < 0.001; social: β = −0.25, p < 0.001; environmental: β = −0.20, p < 0.001). Conclusions: DED significantly affects all QoL domains. Risk factors include occupation, diabetes, hypertension, and thyroid disorders. Awareness and prevention efforts should be prioritized by institutions, while physicians should screen for DED in patients with chronic conditions. Further research is needed on the long-term effects of these risk factors and to improve management strategies.